Benefits and harms of interventions to improve anxiety, depression, and other mental health outcomes for autistic people: A systematic review and network meta-analysis of randomised controlled trials. (January 2023) - Linden, Audrey; Best, Lawrence; Elise, Freya; Roberts, Danielle; Branagan, Aoife; Tay, Yong Boon Ernest; Crane, Laura; Cusack, James; Davidson, Brian; Davidson, Ian; Hearst, Caroline; Mandy, William; et al.
Mental health difficulties are prevalent in autistic people with 14%–50% having experienced depression and 40%–80% having experienced anxiety disorders. Identifying interventions that improve autistic people's mental health is a top priority. However, at present, there is no high-quality network meta-analysis of benefits and harms of different interventions. We conducted a systematic review and network meta-analysis of randomised controlled trials, searching MEDLINE, EMBASE, other databases, and trial registers until 17 October 2020. We included randomised controlled trials reporting anxiety or depression in a suitable format. We calculated effect estimates and 95% credible intervals using Bayesian network meta-analysis. Our search identified 13, 794 reports, of which 71 randomised controlled trials (3630 participants) were eligible for inclusion. All trials had high risk of bias. The follow-up period ranged from 1 to 24 months. Evidence indicates uncertainty about the effects of different interventions, with more high-quality evidence needed. Available evidence suggests that some forms of cognitive behavioural therapy may decrease anxiety and depression scores in autistic children and adults; mindfulness therapy may decrease anxiety and depression scores in autistic adults with previous mental health conditions; and behavioural interventions may provide some benefit for depression in autistic children. We recommend that autistic people are given access to mental health interventions available to non-autistic people, following principles of person-centred care. PROSPERO registration ID: CRD42019136093 Lay Abstract: Nearly three out of four autistic people experience mental health problems such as stress, anxiety or depression. The research already done does not guide us on how best to prevent or treat mental health problems for autistic people. Our aim was to look at the benefits and harms of different interventions on mental health outcomes in autistic people. We searched all the published randomised controlled trials (RCTs) about interventions for mental health conditions in autistic people until 17 October 2020. We also searched for RCTs that were not published in peer-reviewed journals. These were obtained from registers of clinical trials online. We then combined the information from all these trials using advanced statistical methods to analyse how good the interventions are. Seventy-one studies (3630 participants) provided information for this research. The studies reported how participants were responding to the intervention for only a short period of time. The trials did not report which interventions worked for people with intellectual disability. In people without intellectual disability, some forms of cognitive behavioural therapy and mindfulness therapy may be helpful. However, further research is necessary. Many trials used medications to target core features of autism rather than targeting mental health conditions, but these medications did not help autistic people. Until we have more evidence, treatment of mental health conditions in autistic people should follow the evidence available for non-autistic people. We plan to widely disseminate the findings to healthcare professionals through medical journals and conferences and contact other groups representing autistic people.